Evaluation of correct knowledge of key danger signs in pregnancy among antenatal clinic attendees at a tertiary health facility in Nigeria (2016)
Context: Test of knowledge of pregnant women on key danger signs as a marker to assess the quality of information shared during health education at the antenatal clinic (ANC) is desirable. Aim: The aim was to assess correct knowledge of danger signs among pregnant women who attend ANC. Settings and Design: A cross-sectional design conducted among pregnant women at the ANC of the University College Hospital, Ibadan, Nigeria. Materials and Methods: A pretested structured questionnaire that contains sociodemographics, past obstetrics history, and a list of test questions to assess correct knowledge of danger signs was administered to each consenting participant. Statistical Analysis Used: Descriptive and bivariate analyses were performed. The knowledge score of key danger signs in pregnancy (KDSP) was measured on a scale of 0–7 and participants were scored as having poor (0–2), fair (3–4), or good (5–7) knowledge. The reliability of the questionnaire to assess knowledge score was determined with Cronbach’s alpha. Statistical significance was set 5%. STATA 12.0 Software was used. Results: The mean age of respondents was 30.28 ± 4.56 with the majority (75.1%) of respondents aged 26–35 years. The Cronbach’s alpha was 0.871. In general, the knowledge score was good and the associated factors on bivariate analysis were younger age (P = 0.028), Islamic religion (P = 0.048), ethnicity (P = 0.03), professional occupation (P = 0.01), and previous attendance of health talk on KDSP (P < 0.0001). Conclusion: There was a high knowledge score of KDSP, but some still have some misconceptions that need to be addressed.